Dispatches from the field: sociality and reproductive success in prairie voles. (September 2018) - Solomon, Nancy G.; Keane, Brian
Abstract : One way to characterize sociality is by the type and variability of social organization exhibited by individuals within populations. Social unit size and composition can result in costs and benefits to female group members, which may affect their reproductive success. We tested this hypothesis using data from two natural populations of prairie voles, Microtus ochrogaster, that live in habitats differing in the distribution of vegetation and in population density. During short-term investigations of populations in Indiana and Kansas (4–8 weeks), we detected significant differences between populations in the type of social units in which adult females resided, with most adult females in Kansas living as single females, whereas in Indiana most females resided in groups. However, neither social unit size nor composition was related to female reproductive success in either population. When we studied the same Indiana population for 15 weeks, the length of time that females were detected on the study grid or were residents at a nest predicted the number of offspring they produced. In addition, the number of offspring produced by females tended to decrease with group size, although this relationship was not statistically significant. Finally, social unit size was not significantly related to the amount of time females were detected in the population. Our results suggest that females do not obtain increased direct or indirect fitness by living in larger groups. Rather, persistence and residency status of females in the population are the best predictors of female reproductive success. Highlights: We examined effects of group size and composition on female reproductive success. We did not find significant effects in our short-term field seasons. Females with longer survival and residency had greater reproductive success. Breeding females in large groups did not obtain increased fitness. Future studies should examine factors influencing survival of breeding females.